Descriptive Cost-Effectiveness Analysis of a Counseling and Coordination Model in Psychosocial Care. Integration of Health Care and Social Rehabilitation - Berghöfer, Anne; Hense, Sabrina; Birker, Thomas; Hejnal, Torsten; Röwenstrunk, Frank; Albrecht, Marion; Erdmann, Daniela; Reinhold, Thomas; Stöckigt, Barbara (Frontiers in Psychiatry, 2020)
Introduction: A psychosocial outreach clinic was established to offer counseling and coordination of healthcare and complementary services for persons with psychosocial and mental problems. The cost-effectiveness of these services was measured based on a pre-post comparison. Methods: A prospective observational study was conducted with clients of the outreach clinic. Data on resource consumption and quality of life were collected at baseline and follow-up after 3, 6, and 12 months using the Client Sociodemographic And Service Receipt Inventory to assess service utilization, and the 12-Item Short Form Health Survey to assess quality of life. The objective of the present analysis was to estimate the relation between monetary expenditure and QALYs (quality-adjusted life-years), before and after the outreach clinic was established, descriptively. The analysis was constructed from payer’s perspective and was supplemented by a sensitivity analysis. Results: A total of 85 participants were included. Total annual expenditures before the intervention were 5,832 € per client for all service segments. During the 12-months study duration expenditures decreased to 4,350 € including the costs associated with outreach clinic services. QALYs for the 12-month study period were 0.6618 and increased about 0.0568 compared to the period before. Discussion: Despite methodological limitations due to small sample size, a pre-post comparison and the retrospective cost data collection, this study suggests acceptability of the outreach clinic as cost-effective. Conclusion: The activities of the outreach clinic as an integrated care model seem to be cost-effective regarding the relation between monetary expenditures and clients’ quality of life.